The Oxidative Acylnitroso Hetero-Diels–Alder Reaction Catalyzed by Dirhodium Caprolactamate - Tusun, Xiarepati; Lu, Chong-Dao (Synlett, 2012)
An effective protocol is described for the generation and in situ Diels–Alder trapping of acylnitroso derivatives. In this procedure, the oxidation of hydroxamic acid is efficiently catalyzed by dirhodium(II) caprolactamate with tert-butyl hydroperoxide (TBHP) in the presence of dienes at room temperature. Using this approach we obtained a variety of hetero-Diels–Alder cycloadducts in yields of up to 96% at 0.1 mol% catalyst loading.
Keywords: catalysis; oxidation; acylnitroso; Diels–Alder reaction; dirhodium(II)